Can brazilian consumer foresee their future behavior during the pandemic? - Oliveira, Wiviany Ferreira de (2021)
Objective - The objective of the study is to examine if the changes in consumer behavior brought about by the COVID-19 pandemic are permanent and if consumers can make predictions about their future consumption patterns. Design/Methodology - The present dissertation applied a longitudinal survey. In Phase 1, before the availability of the vaccine, the frequency of consumption behaviors (in December 2020) was analyzed in a questionnaire and, alongside these questions, participants also indicated their predictions of future behavior after vaccines become available. In phase 2, in May 2021, we inspected if the consumers' predictions were accurate, through the reapplication of the questionnaire. Findings - The results show that consumers can accurately predict future behavior regarding app-based food shopping and online clothing shopping. Despite the absence of statistical significance, participants were wrong about the direction of their future behavior in terms of alcohol consumption and online grocery shopping. Critically, the only behavior that participants were blatantly wrong about was related to physical activities. When it comes to such behavior, their expectations about the future clearly exceeded their actions. Research limitations – The study’s main limitations refer to reliance of self-reported behavior rather than actual behavior, the small sample size at time 2 (n=46) relative to time 1 (n=149), and the fact that the pandemic was still underway during our “post-vaccination” period. Practical implications - The research produced valuable insights on whether consumers are able to predict future behavior, which is central to marketing research. In doing so, it also offers relevant information about how marketing strategies can interfere in consumer behavior.